Surgery is not a game: the importance of human centered design in medical extended reality device development - Dhanaliwala, Ali H.; Egeth, Marc; Privitera, Mary Beth (Frontiers in Virtual Reality, 2025)
The use of virtual, augmented, and/or mixed reality in applications targeting medical indications is rapidly growing. A main driver has been the rapid progress in wearable computing, specifically headsets. Yet, most of the headsets currently used for medical applications were not designed specifically for use in medicine, potentially accounting for undesired outcomes and limited adoption. Human Factors (HF) engineering is a design philosophy and methodology which seeks to inform technological development through understanding of human capabilities and limitations. We believe a HF engineering approach is essential when designing for a high stakes environment such as medicine to achieve a useful, and usable extended reality (XR) headset. In this paper, we will briefly review the history of XR headsets and outline the key components of HF engineering. Next, we present a series of real-world experiences depicting utilization of XR headsets in the clinical workflow to illustrate the potential and shortcomings of the current technology. Finally, we introduce medicalextendedreality.com as a forum for gathering user requirements which can be used in the design of future headsets intended for medical use.